Estimation of radiation dose to patients from (18)FDG whole body PET/CT investigations using dynamic PET scan protocol - Kaushik, Aruna (Indian J Med Res, 2015)
BACKGROUND & OBJECTIVES: There is a growing concern over the radiation exposure of patients from undergoing (18)FDG PET/CT ((18)F-fluorodeoxyglucose positron emission tomography/computed tomography) whole body investigations. The aim of the present study was to study the kinetics of (18)FDG distributions and estimate the radiation dose received by patients undergoing (18)FDG whole body PET/CT investigations. METHODS: Dynamic PET scans in different regions of the body were performed in 49 patients so as to measure percentage uptake of (18)FDG in brain, liver, spleen, adrenals, kidneys and stomach. The residence time in these organs was calculated and radiation dose was estimated using OLINDA software. The radiation dose from the CT component was computed using the software CT-Expo and measured using computed tomography dose index (CTDI) phantom and ionization chamber. As per the clinical protocol, the patients were refrained from eating and drinking for a minimum period of 4 h prior to the study. RESULTS: The estimated residence time in males was 0.196 h (brain), 0.09 h (liver), 0.007 h (spleen), 0.0006 h (adrenals), 0.013 h (kidneys) and 0.005 h (stomach) whereas it was 0.189 h (brain), 0.11 h (liver), 0.01 h (spleen), 0.0007 h (adrenals), 0.02 h (kidneys) and 0.004 h (stomach) in females. The effective dose was found to be 0.020 mSv/MBq in males and 0.025 mSv/MBq in females from internally administered (18)FDG and 6.8 mSv in males and 7.9 mSv in females from the CT component. For an administered activity of 370 MBq of (18)FDG, the effective dose from PET/CT investigations was estimated to be 14.2 mSv in males and 17.2 mSv in females. INTERPRETATION & CONCLUSIONS: The present results did not demonstrate significant difference in the kinetics of (18)FDG distribution in male and female patients. The estimated PET/CT doses were found to be higher than many other conventional diagnostic radiology examinations suggesting that all efforts should be made to clinically justify and carefully weigh the risk-benefit ratios prior to every (18)FDG whole body PET/CT scan.